Comparing clinical outcomes in HIV‐infected and uninfected older men hospitalized with community‐acquired pneumonia. Issue 7 (11th May 2015) - Barakat, LA; Juthani‐Mehta, M; Allore, H; Trentalange, M; Tate, J; Rimland, D; Pisani, M; Akgün, KM; Goetz, MB; Butt, AA; Rodriguez‐Barradas, M; Duggal, M; et al.
<x xml:space="preserve">Abstract</x> Objectives Outcomes of community–acquired pneumonia (CAP) among HIV‐infected older adults are unclear. Methods Associations between HIV infection and three CAP outcomes (30‐day mortality, readmission within 30 days post‐discharge, and hospital length of stay [LOS]) were examined in the Veterans Aging Cohort Study (VACS) of male Veterans, age ≥ 50 years, hospitalized for CAP from 10/1/2002 through 08/31/2010. Associations between the VACS Index and CAP outcomes were assessed in multivariable models. Results Among 117 557 Veterans (36 922 HIV‐infected and 80 635 uninfected), 1203 met our eligibility criteria. The 30‐day mortality rate was 5.3%, the mean LOS was 7.3 days, and 13.2% were readmitted within 30 days of discharge. In unadjusted analyses, there were no significant differences between HIV‐infected and uninfected participants regarding the three CAP outcomes (P > 0.2). A higher VACS Index was associated with increased 30‐day mortality, readmission, and LOS in both HIV‐infected and uninfected groups. Generic organ system components of the VACS Index were associated with adverse CAP outcomes; HIV‐specific components were not. Among HIV‐infected participants, those not on antiretroviral therapy (ART) had a higher 30‐day mortality (HR 2.94 [95% CI 1.51, 5.72]; P = 0.002) and a longer LOS (slope 2.69 days [95% CI 0.65, 4.73]; P = 0.008), after accounting for VACS Index. Readmission was not associated with ART use (OR 1.12 [95% CI 0.62, 2.00] P = 0.714). Conclusion Among HIV‐infected and uninfected older adults hospitalized for CAP, organ system components of the VACS Index were associated with adverse CAP outcomes. Among HIV‐infected individuals, ART was associated with decreased 30‐day mortality and LOS.